Response of Plant Community Characteristics and Soil Factors to Topographic Variations in Alpine Grasslands - Qinyang Liang; Jinmei Zhao; Zixin Wang; Xingyi Wang; Dianxia Fu; Xiaogang Li (Plants)
Topography has an important influence on plant–soil relationships. However, research on plant–soil relationships in alpine grassland at the slope aspect and slope position scales is currently inadequate. In this paper, based on the topographic and geomorphological characteristics of the study area, alpine grassland with typical slope aspect and slope position conditions was selected as the research object. Through field investigations and laboratory research to reveal how the characteristics of the alpine grassland plant community and soil factors respond to changes in topography. The results show: Slope aspect and slope position changes significantly affect alpine grassland plant communities and soil properties. In terms of the dominant species in plant communities, the sunny slopes were dominated by Poaceae and the shady slopes were dominated by Polygonaceae. Plant community characterization variables showed a decreasing trend from shady to sunny slopes and bottom to top. The soil factors showed significant differences among the six types of topography (p < 0.05), and the magnitude order in different slope aspects and positions was basically shady slope > sunny slope and bottom > middle and top. Correlation analysis showed that there were good correlations between soil organic carbon (SOC), soil water content (SWC), total nitrogen (TN), pH, and plant community characteristics in alpine grassland. In addition, redundancy analyses (RDA) indicated that the divergence in plant community characteristics was primarily driven by the change difference in SOC along topographic gradients. Our findings may provide a scientific basis for the restoration and utilization of alpine grassland vegetation and the evaluation of the ecological environment in this region.